PRECICE® magnetically-driven, telescopic, intramedullary lengthening nail: pre-clinical testing and first 30 patients - Wagner Pablo; Burghardt Rolf D.; Green Stuart A.; Specht Stacy C.; Standard Shawn C.; Herzenberg John E. (SICOT-J, 2017)
Introduction: Femoral/tibial lengthening with a telescopic, magnetically-powered, intramedullary nail is an alternative to lengthening with external fixation.